2004
DOI: 10.1897/03-266
|View full text |Cite
|
Sign up to set email alerts
|

Physical and biochemical interactions of soil fungi with asbestos fibers

Abstract: Iron, a structural component of most asbestos, is thought to play a crucial role in asbestos toxicity. Surface iron favors fiber uptake by mammalian cells and promotes the generation of free radicals with consequent DNA and lipid damage. In some cases, chemical removal of iron from asbestos fibers has reduced several cellular responses to asbestos. Since iron represents an essential element for soil microorganisms, many of them have developed mechanisms to scavenge this element from poorly soluble forms. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Previous ultrastructural studies have shown that the fibrils are, in this case, in intimate contact with the fungus. [24,25] None of the fibers examined significantly inhibited biomass production of F. oxysporum grown in liquid culture (Figure 1), either in direct contact with the fungus or when kept in a separate chamber by a dialysis membrane. The presence of asbestos fibers, however, caused the release of a dark yellow soluble pigment in the culture medium.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Previous ultrastructural studies have shown that the fibrils are, in this case, in intimate contact with the fungus. [24,25] None of the fibers examined significantly inhibited biomass production of F. oxysporum grown in liquid culture (Figure 1), either in direct contact with the fungus or when kept in a separate chamber by a dialysis membrane. The presence of asbestos fibers, however, caused the release of a dark yellow soluble pigment in the culture medium.…”
Section: Resultsmentioning
confidence: 95%
“…[2,16,17,36,37] Biochemical response of fungi to asbestos fibers: Modification in protein expression: The modification in protein expression following interaction with asbestos may be a fungal response either to physical contact with the fibers or to a possible oxidative stress caused by the fiber or by mobilized iron. The SEM analysis of mycelia grown in direct contact with the fibers showed the physical integrity of hyphae; [25] thus, the extracellular protein pool changes in the presence of fibers are likely to be due to active synthesis. Protein induction or inhibition due to stress is reported in several studies on fungi and other microorganisms, [38][39][40][41] particularly for metal-induced stress, for example, extracellular protein induction in ericoid fungi grown in the presence of zinc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbes convert metal compounds into their water soluble forms and are biocatalysts of leaching processes. Many microbes have mechanisms that enable access to ion from poorly soluble forms (Martino et al, 2004). One possible way to obtain iron from low grade ores is through the microbial leaching.…”
Section: Ajmmentioning
confidence: 99%